Classification and Characteristics of Pain Associated with Parkinson’s Disease - Marcelo Rezende Young Blood; Marcelo Machado Ferro; Renato Puppi Munhoz; Hélio Afonso Ghizoni Teive; Carlos Henrique Ferreira Camargo (Parkinson's Disease)
Neuropsychiatric symptoms and pain are among the most common nonmotor symptoms of Parkinson’s disease (PD). The correlation between pain and PD has been recognized since its classic descriptions. Pain occurs in about 60% of PD patients, two to three times more frequent in this population than in age matched healthy individuals. It is an early and potentially disabling symptom that can precede motor symptoms by several years. The lower back and lower extremities are the most commonly affected areas. The most used classification for pain in PD defines musculoskeletal, dystonic, central, or neuropathic/radicular forms. Its different clinical characteristics, variable relationship with motor symptoms, and inconsistent response to dopaminergic drugs suggest that the mechanism underlying pain in PD is complex and multifaceted, involving the peripheral nervous system, generation and amplification of pain by motor symptoms, and neurodegeneration of areas related to pain modulation. Although pain in DP is common and a significant source of disability, its clinical characteristics, pathophysiology, classification, and management remain to be defined.